2018
DOI: 10.3892/or.2018.6714
|View full text |Cite
|
Sign up to set email alerts
|

Radioresistant breast cancer cells exhibit increased resistance to chemotherapy and enhanced invasive properties due to cancer stem cells

Abstract: Previous studies suggest that cancer stem cells (CSCs) exist in solid tumors, and contribute to therapeutic resistance and disease recurrence. Therefore, the present study aimed to investigate whether radioresistant (RT-R) breast cancer cells derived from breast cancer cells increase the number of CSCs, and whether these CSCs are responsible to increased invasiveness and therapeutic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 32 publications
0
71
1
Order By: Relevance
“…In this study, several markers-CD44 and Oct-3/4 (octamer-binding transcription factor 3/4), βcatenin, and MMP-9-were chosen for RT resistance, for they were significantly increased after acquiring resistance to RT in previous study [9]. In addition, they are related to CSCs, cancer progression, and EMT.…”
Section: Pkal Significantly Inhibited Expression Of Stem Cell Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, several markers-CD44 and Oct-3/4 (octamer-binding transcription factor 3/4), βcatenin, and MMP-9-were chosen for RT resistance, for they were significantly increased after acquiring resistance to RT in previous study [9]. In addition, they are related to CSCs, cancer progression, and EMT.…”
Section: Pkal Significantly Inhibited Expression Of Stem Cell Markersmentioning
confidence: 99%
“…Our team previously established radio-resistant MDA-MB 231 human breast cancer cells (RT-R-MDA-MB 231 cells) which exhibit enhanced aggressiveness, and cancer stem cell features [9,10]. These cells also manifest epithelial-mesenchymal transition (EMT), a process by which epithelial cells gain migratory and invasive properties to become mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notch4 signaling promotes breast cancer cell survival in response to diverse treatment modalities [18][19][20] and is implicated in poor prognosis and high risk of relapse in breast cancer patients 21 . Notch4 signaling regulates susceptibility to cell death in human B cell acute lymphoblastic leukemia 1 , endothelial 3 , as well as cells of pancreatic origin 22 among others.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy is one of the most effective breast cancer treatment strategies which significantly improves the therapeutic outcome and survival of breast cancer patients (Moran et al, 2015;Bartelink et al, 2001;Fisher et al, 1995;Cun et al, 2013). Resistance to radiation represents one of the important challenges for breast cancer radiotherapy effectiveness including triple negative breast cancer (Ko et al, 2018;Qi et al,2017;He et al, 2018) which represent the most radio-resistant breast cancer (He et al, 2018;Kyndi et al, 2008). In the present study, found that TMPRSS4 inhibition increased TNBC cell radio-sensitivity ( Figure 1A, B, C) and improved the cell proliferation reduction mediated by IR ( Figure 2C).…”
Section: Discussionmentioning
confidence: 99%